2001
DOI: 10.1177/014107680109401007
|View full text |Cite
|
Sign up to set email alerts
|

Students Sitting Medical Finals–-Ready to be House Officers?

Abstract: An initial survey of students approaching qualification and the preregistration house officer year revealed anxiety about competence in several important clinical skills. A questionnaire study was then undertaken to assess, first, the extent to which students had attained the skills required for the preregistration year and, second, the amount of training in these skills provided during the preregistration year. 122 medical students taking their final examinations were asked about training and practice in eigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
41
1
7

Year Published

2003
2003
2013
2013

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 11 publications
(10 reference statements)
2
41
1
7
Order By: Relevance
“…with actual clinical experience [13,14] Since the practice of medicine involves a level of apprenticeship, many of the duties of HOs expose them rather prematurely to handling potentially hazardous sharp instruments and objects (e.g. setting up lines, venepuncture [13,15], as well as taking blood samples, saliva for laboratory testing, and tissues for biopsies).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…with actual clinical experience [13,14] Since the practice of medicine involves a level of apprenticeship, many of the duties of HOs expose them rather prematurely to handling potentially hazardous sharp instruments and objects (e.g. setting up lines, venepuncture [13,15], as well as taking blood samples, saliva for laboratory testing, and tissues for biopsies).…”
mentioning
confidence: 99%
“…setting up lines, venepuncture [13,15], as well as taking blood samples, saliva for laboratory testing, and tissues for biopsies). Additionally, dental HOs administer local anesthetics in procedures like simple tooth extraction, root canal fillings, and restorations; and they use instruments such as sharp forceps and elevators.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This and other studies found self-assessment of competence by students to be positively correlated with their frequency of procedure performance [14,15]. Goodfellow et al [16] surveyed 122 final-year medical students at a UK university, in eight ''core'' clinical skills, and found that the majority of these skills had been performed few times by students over their entire undergraduate course. A Dutch study showed that medical schools cannot rely on clerkships to train students in basic clinical skills to the expected standard [17].…”
Section: Discussionmentioning
confidence: 86%